Advanced post-treatment strategy for quantum-grade fluorescent nanodiamonds - Alkahtani, Masfer H.; Alzahrani, Yahya A.; Hazrathosseini, Ayla; Alessa, Abdulmalik M.; Sow, Maabur; Alromaeh, Abdulaziz; Alghihab, Abdulrahman A.; Alghannam, Faisal S.; Jelezko, Fedor; Hemmer, Philip R. (Frontiers in Quantum Science and Technology, 2025)
Fluorescent nanodiamonds (FNDs) containing nitrogen-vacancy (NV−) centers are promising platforms for quantum sensing and bioimaging, but their performance is often limited by surface defects, residual graphitic carbon, and ionic contamination. Here, we report a multistep surface treatment strategy combining molten potassium nitrate (KNO3) thermal oxidation with sequential acid and alkaline cleaning to produce high-quality, quantum-grade FNDs. Molten KNO3 etching at 580 °C enables morphological reshaping and partial oxidation, while subsequent H2SO4/HNO3, NaOH, and HCl washes eliminate graphitic residues, neutralize surface charges, and remove metal ions. This protocol yields discrete, colloidally stable FNDs with enhanced photoluminescence, a high ODMR contrast of 11.5%, and extended average spin-lattice relaxation time (T1 ≈ 2045 µs). Dynamic light scattering and ζ-potential measurements confirm excellent dispersion (∼100 nm, −30 mV). The integration of chemical, morphological, and spin-performance improvements establishes a scalable route for producing FNDs suitable for high-fidelity quantum sensing and biophotonic applications.